Desain Beton Dengan Menggunakan Sisa Bakaran Bata Merah Sebagai Bahan Pengisi Beton - Pattirousamal, Marnes; Tonny Sahusilawane; Abraham Tuanakotta (Unmuh Babel Press, 2024)
Concrete is part of a building that we often come across in construction, such as buildings, roads and Bridges. The main components of concrete are sand, shattered rock and water. Concrete is a common material as people grow in need of infrastructure over time. With today's rapid infrastructure development, innovation in concrete is always needed to address demand challenges. Research methods are employed in the ambon state polytechnique laboratory, where materials inspection and strong tests of concrete are used, which USES the rest of red bricks as raw aggregate added 5% and reduction of 5% size red bricks 1/2 and 2/3. Test results of strong concrete pressure with red brick residue 5% increased and reduced significantly to strong normal concrete pressure.